2015
DOI: 10.1177/1355819615577711
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the persistence of health expenditures and the implications for the design of capitation payments in Taiwan

Abstract: Given the increase in predictive ability, adding chronic conditions and baseline health care use data to Taiwan's capitation payment formula would correctly identify more high users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…Given Sefehri’s conclusion and the result of this study, we could infer that families with children under 6 years old may utilize more medical services but do not spend much because the entire family may be relatively younger (average age 32.15 ± 5.96, families without children: 43.58 ± 12.73), healthier, and would use more outpatient rather than inpatient services. In addition, families with the elderly over 60 years old were not taken as potential predictors for high expenditure, which seemed to be in contrary to many previous studies [7,30]. However, upon further consideration, we could explain that the key determinant of HC families was not whether the family had old members but whether the old members had poor health status and increased healthcare utilization.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Given Sefehri’s conclusion and the result of this study, we could infer that families with children under 6 years old may utilize more medical services but do not spend much because the entire family may be relatively younger (average age 32.15 ± 5.96, families without children: 43.58 ± 12.73), healthier, and would use more outpatient rather than inpatient services. In addition, families with the elderly over 60 years old were not taken as potential predictors for high expenditure, which seemed to be in contrary to many previous studies [7,30]. However, upon further consideration, we could explain that the key determinant of HC families was not whether the family had old members but whether the old members had poor health status and increased healthcare utilization.…”
Section: Discussioncontrasting
confidence: 73%
“…It is seems an universal phenomenon that a vital few population (or families) accounts for a large proportion of the total expenditure, no matter what health insurance scheme or health delivery system and how the economic developed. It is true for the United States, with a its commercial health insurance system, for several European countries [5,6], and China (the mainland) with statutory health insurance system, and even for Taiwan, which has a similar national health service system to that of the United Kingdom [7]. For economically developed countries, health projects or plans could be implemented to reduce unreasonable and avoidable health service utilization, since some actions have already turned out valuable in the United States [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the top 10%, top 5%, and top 1% high-cost patients roughly account for, respectively, 68%, 55%, and 24% of costs within a given year [3]. A few studies from the United States, European countries, Hong Kong, and Taiwan, all with different health insurance schemes and healthcare delivery systems, have presented similar findings [4,5,6,7,8]. These findings suggest that high-cost patients are a logical group to seek for cost-reduction financial support; caring for this group is an urgent priority [9].…”
Section: Introductionmentioning
confidence: 78%
“…The vast majority (n=42) of the publications originated from the USA, nine were from Canada, three were generated by researchers from European countries and one was from Taiwan. Compared with nine US-based studies of the Medicare (ie, senior) population, only the study from Taiwan among the others had a specific focus on seniors, even though approximately 45%–55% of senior healthcare care resources are reportedly consumed by senior HCUs in various jurisdictions 10–12. Moreover, these studies do not differentiate between prevalent (who retain the HCU status over years) and incident senior HCUs.…”
Section: Introductionmentioning
confidence: 99%